2020
DOI: 10.1016/j.aca.2020.03.062
|View full text |Cite
|
Sign up to set email alerts
|

Miniaturized weak affinity chromatography for ligand identification of nanodiscs-embedded G-protein coupled receptors

Abstract: Biophysical techniques that enable the screening and identification of weak affinity fragments against a target protein are at the heart of Fragment Based Drug Design approaches. In the case of membrane proteins, the crucial criteria for fragment screening are low protein consumption, unbiased conformational states and rapidity because of the difficulties in obtaining sufficient amounts of stable and functionally folded proteins. Here we show for the first time that lipidnanodisc systems (membrane-mimicking en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 58 publications
0
34
0
Order By: Relevance
“…Among others, two studies reported promising fragment screening using Weak Affinity Chromatography (WAC) including for a GPCR target. 69 , 70 It will be interesting to see if these exploratory studies will result in lead compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Among others, two studies reported promising fragment screening using Weak Affinity Chromatography (WAC) including for a GPCR target. 69 , 70 It will be interesting to see if these exploratory studies will result in lead compounds.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of the secondary binding agent may also increase the possibility for non‐specific binding and result in a lower binding capacity for the affinity ligand due to steric hindrance. Biospecific adsorption in AMC has been used to prepare monoliths for the capture of antibodies by protein A or protein G; in addition, streptavidin monoliths have been used to adsorb biotinylated HSA, aptamers, and membrane proteins [60,64,172,187,198–200].…”
Section: Immobilization Methods For Affinity Monolithsmentioning
confidence: 99%
“…Frontal analysis using affinity monoliths coupled with MS has been applied to examine the binding of small molecules to dihydrofolate reductase [90] and to examine small ligands that may bind to adenosine A 2A receptor and compete with theophylline for this receptor (see Fig. 9) [200]. AMC has also been used in a frontal analysis format to examine the binding of IgG to protein A, protein G, and protein L [170,178,325].…”
Section: Applications Of Amcmentioning
confidence: 99%
“…Avidin has recently been used with biotin and affinity columns in various formats to isolate proteins under native elution conditions [171]. Streptavidin-biotin interactions have also been employed in miniaturized affinity systems to identify and characterize ligands for nanodisc-embedded G-protein coupled receptors [172].…”
Section: Biological Binding Agentsmentioning
confidence: 99%